Hubungan Health Belief Model dan Perilaku Merokok Pada Mahasiswa - Sinaga, Diana Elysabeth; Savira, Siti Ina (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Students are in time emerging adults with a higher level of susceptibility to smoking. Health belief model is effective in explaining smoking behavior in students. This research aims to determine the relationship health belief model and smoking behavior in students. Quantitative methods were used in this research by distributing questionnaires on line. The research sample consisted of 272 male students, who had consumed at least 100 cigarettes during their lives, and were still smoking today. Based on the results of correlation analysis using pearson product moment it is known that the variable health belief model and smoking behavior has a significant relationship, namely 0.000 (p<0.05) with the strength of the correlation in the medium category and the direction of the relationship is negative.